2021
DOI: 10.22541/au.161326888.88111707/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic Cardiac Autonomic Nervous System: what do clinical electrophysiologists need to know about the ‘heart brain’?

Abstract: It is increasingly recognized that the autonomic nervous system (ANS) is a major contributor in many cardiac arrhythmias. Cardiac ANS can be divided into extrinsic and intrinsic parts according to the course of nerve fibers and localization of ganglia and neuron bodies. Although the role of extrinsic part has historically gained more attention, the intrinsic cardiac ANS may affect cardiac function independently as well as influence the effects of the extrinsic nerves. Catheter based modulation of the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Chemical phenotype of a neuron may be indicative of its function and, therefore, the shift in proportions of particular neuronal phenotypes provides the anatomical basis for adaptability of ICNs as this was clearly demonstrated for the heart rate decreases in respect to age of some animal species following shift in abundance of neurons in the sympathetic chain ganglia (Woods et al, 1977; Yiallourou et al, 2012). Since both, the chemical phenotype and the location of ICNs, may be strongly associated with their function, an analysis of distribution of the phenotypically distinct ICNs should contribute to disclosure of the genuine cause of different structural patterns of GP in diverse animal species (Aksu et al, 2021; Brack, 2015; Hanna et al, 2021). Furthermore, the widespread neural communications with and between ICNs ensure an integration of the extrinsic and intracardiac signals within GP in which the interplay between cholinergic, adrenergic, and other chemical phenotypes of ICNs occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical phenotype of a neuron may be indicative of its function and, therefore, the shift in proportions of particular neuronal phenotypes provides the anatomical basis for adaptability of ICNs as this was clearly demonstrated for the heart rate decreases in respect to age of some animal species following shift in abundance of neurons in the sympathetic chain ganglia (Woods et al, 1977; Yiallourou et al, 2012). Since both, the chemical phenotype and the location of ICNs, may be strongly associated with their function, an analysis of distribution of the phenotypically distinct ICNs should contribute to disclosure of the genuine cause of different structural patterns of GP in diverse animal species (Aksu et al, 2021; Brack, 2015; Hanna et al, 2021). Furthermore, the widespread neural communications with and between ICNs ensure an integration of the extrinsic and intracardiac signals within GP in which the interplay between cholinergic, adrenergic, and other chemical phenotypes of ICNs occurs.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, anatomical studies on the mammalian heart mostly focused on determining the location of autonomic ganglia using the histologic examination of heart sections, resulting in the concept of GPs consisting of grouping ganglia in different atrial sites. 6 According to anatomical based GP nomenclature by Armour et al 7 is compatible with the anatomical localization of Armour's. We believe that one reason for this discrepancy may be that HFS may stimulate not only epicardial ganglia but also nerves that extend from epicardial ganglia towards the atrial regions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Morphological studies have shown that although most autonomic ganglia are embedded within the epicardium, there is a highly dense network of sensory and efferent nerve fibers at the myocardial and endocardial levels. 2,7,8 Notably, the highest density of autonomic innervation is found at the pulmonary vein-atrial junction. 9 However clinical studies correlating the findings of these anatomical studies are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Acute neuromodulation effects are often observed during PVI procedures, and several groups have shown that both intra‐procedural vagal effects as well as post‐procedural sympathetic effects are associated with improved arrhythmia free survival 5,6 . Morphological studies have shown that although most autonomic ganglia are embedded within the epicardium, there is a highly dense network of sensory and efferent nerve fibers at the myocardial and endocardial levels 2,7,8 . Notably, the highest density of autonomic innervation is found at the pulmonary vein–atrial junction 9 .…”
Section: Discussionmentioning
confidence: 99%